PENGARUH TEMPERATUR DALAM PEMBUATAN KARBON AKTIF DARI KULIT SALAK (SALACCA SUMATRANA) DENGAN AKTIFATOR SENG KLORIDA (ZnCl2) - Muhammad Turmuzi, Ardiano Oktavianus Sahat Tua, Fatimah (Jurnal Teknik Kimia USU, 2015)
Activated carbon can be made of organic or anorganic materials. Salak peel is a potential organic material as activated carbon. This research aimed to understand the effect of temperature in activated carbon with chemical activation ZnCl2 production from salak peel. The method included preparation of raw material, chemical activation, pyrolysis and iodine value test. The ratio of ZnCl2 is1:1 g/g, the activation time is 2 hours and the acivation temperature variation is 400, 450, 500, 550 and 600 oC. Results showed that the iodine value increased and yield decreased as the increasing of activation temperature. The highest iodine value and yield were achieved at 600°C and 400°C, the values were 694 mg/g and 30,93%.